IMPLEMENTASI “SUSTAINABLE COMPETITIVE ADVANTAGE (SCA) PADA PERGURUAN TINGGI SWASTA (PTS) - Aridha Prassetya (BALANCE: Economic, Business, Management and Accounting Journal, 2008)
Public universities may  have no difficulties to market their product, because they have had a strong settled brand. The brand which has been stuck on  the mind of public or prospect. These public universities have been trusted for along time ago, especially if we talk about the product quality. Public has an opinion that public university is the best institution  you must choose , because you’ll get your superior dignity from there.Asking anyone about university, whoever will choose the public universtity first, of course. And after that, if they don’t succeed for the selection, they just decide to consider another one (private universitiy). As we know, because of it’s brand, the public university can price its products on whatever level.On the other hand, the prospect doesn’t need any deep consideration for the price. They will pay it, no matter about the price. Even if it is  so expensive, as long as they can be received as its student. Because “the brand” will give them “the brand” too, in the future.Private university has to face something that rather special, relevant to this difficult condition.  It is worried that public university will get more students than they can reach. It is worried that public university will open more and more classes. They all have to compete, then. This competition  makes them think harder. They’re now,  fighting to find the answer of  “how to win the competition”.As we know, that, winning a competition depends on the ability to create  a competitive advantage. So, they compete to build a competitive advantage, to try to be a different institution compared to others. They make a new department which is called marketing department. This department is expected to handle any marketing problems. The goal is one. It is “winning the competition”.   The question is “ is it enough to build a competitive advantage?” And the answer is “No, it is not. It’s not enough just building a competitive advantage”. We need something called “Sustainable Competitive Advantage (SCA)”. How to build an SCA? This following article will explain deeply.